Effects of isothermal annealing on the microstructure and mechanical properties of SiC ceramics hot-pressed with Y2O3 and Al2O3 additions - Cheong, DI; Kim, J; Kang, SJL (ELSEVIER SCI LTD, 2002)
Silicon carbide compacts containing various alpha contents and 7 wt.% Of Y2O3 and Al2O3 (weight ratio 60:40) were hot-pressed and isothermally annealed at 1950 degreesC to study the coarsening behavior of SiC grains and the crystallization of the grain-boundary glass phase. The samples which were prepared from the powder compacts containing small amounts of the alpha phase contained well-developed large plate-like grains in fine matrix grains and showed enhanced fracture toughness. A subsequent isothermal annealing was effective in controlling the grain boundary phase and resulted in the enhancement of mechanical properties. When the crystallization of the grain boundary phase leads to an aluminum-rich phase (Y-Al garnet) during the intermediate stage of annealing, flexural strength is improved. On the other hand, the fracture toughness can be increased when crystallization of the grain boundary glass is directed to an yttrium-rich phase during extended annealing. These results were explained in terms of the thermal mismatch between the SiC grain and the remaining glassy phase. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: TOUGHENED SILICON-CARBIDE; FRACTURE-TOUGHNESS; TRANSFORMATION; CHEMISTRY; ROLES; SI3N4